Map of Nova Scotia, New Brunswick, Prince Edward Island and Cape Breton (Dominion of Canada) 1900 - Sydney A. Fisher (Producer)
A regional map of New Brunswick, Nova Scotia, Cape Breton, and Prince Edward Island. Includes the names of bodies of water, counties (and their boundaries), cities and towns. Railway lines are marked and labelled throughout. Scale is 1 : 1,250,000. Material digitized as part of an Academic Innovation Fund (AIF), awarded in 2018. For more information see: http://avptl.info.yorku.ca/academic-innovation-fund/ .